What myths about green technology innovation and financial performance's relationship? A bibliometric analysis review - Lingli Qing; Dongphil Chun; Young-Seok Ock; Abd Alwahed Dagestani; Xiang Ma (Economies, 2022)
The relationship between green technology innovation and corporate financial performance has gained considerable traction in academics and businesses. However, there is limited overall bibliometric analysis on this topic. To meet the research need, this study, using Citespace (Citespace5.8r3 version, ChaomMei Chen, Philadelphia), performed the bibliometric analysis of the relationship between green technology innovation and corporate financial performance from 2007 to 2021, with 251 academic papers published in the Web of Science databases being analyzed, thus identifying the research hotspots and trends. The results showed that: (i) the number of publications has moved from slow to rapid growth and is expected to ramp up further; (ii) only a small collaboration network has been formed among the authors; (iii) institutions' work operates relatively independently. There is still more room for inter-institutional or cross-discipline cooperation against geographical regions. However, there is a strong network of cooperation among countries. China performs best in this research area, followed by Spain and the UK; (iv) several significant co-citation relationships are also formed in the literature network. The burst literature on green innovation, product innovation, and financial performance is considered a research hotspot; and (v) 'green innovation', 'corporate performance', 'legitimacy', 'environmental disclosure', and 'corporate sustainability' have become trends in research. Our results provide academics and practitioners with a robust roadmap on the relationship between green technology innovation and corporate financial performance.
Keywords: 330; bibliometric analysis; Citespace; corporate financial performance; green technology innovation